1988
DOI: 10.1271/bbb1961.52.891
|View full text |Cite
|
Sign up to set email alerts
|

Histamine synthesis by mouse T lymphocytes through induced histidine decarboxylase.

Abstract: Histamine (Hm) mediates and modulates inflammations through a variety of immunoregulatory actions1 '2) and is generally accepted to be released from mast cells and basophil< upon activation of the cells with allergenreagin complex.3) In contrast we have pre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…While we could not detect any increase in histamine or its major metabolite tele-methylhistamine in the conditioned media of PBMCs in the presence of IL-18, the induction of histidine decarboxylase was reported in monocyte/macrophage (26) and T lymphocytes (27) by LPS, IL-1, and TNF-␣ (50). Such inducible histamine appeared to be released after the synthesis without entering into the stable storage pool (26,27,50).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…While we could not detect any increase in histamine or its major metabolite tele-methylhistamine in the conditioned media of PBMCs in the presence of IL-18, the induction of histidine decarboxylase was reported in monocyte/macrophage (26) and T lymphocytes (27) by LPS, IL-1, and TNF-␣ (50). Such inducible histamine appeared to be released after the synthesis without entering into the stable storage pool (26,27,50).…”
Section: Discussionmentioning
confidence: 55%
“…Such inducible histamine appeared to be released after the synthesis without entering into the stable storage pool (26,27,50). Therefore, it is speculated that inducible histamine may regulate the host immune response by modulating cytokine production in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified other histamine-producing cells-monocytes/macrophages (Takamatsu et al 1996), T-lymphocytes (Aoi et al 1989), and vascular endothelial cells (Endo et al 1995)-in which histidine decarboxylase activity was induced by lipopolysaccharide, interleukin-1 ␤ , TNF-␣ , or concanavalin A. Histamine functions as a mediator of inflammation, an immunomodulator, a secretagogue of gastric acid secretion and a neurotransmitter in the CNS. It exerts these effects through the stimulation of three distinct subtypes of receptors, H 1 , H 2 , and H 3 , present on the target cells.…”
mentioning
confidence: 99%
“…Since these cells were found to exhibit relatively high enzyme activity and release histamine spontaneously, they fulfill the requirement for 'inducible' histamine. Although histamine synthesis was also reported in Con A-activated T lymphocytes previously (11), further supporting evidence should be required to establish the concept of T cell-derived histamine.…”
Section: Inducible Histamine Synthesis In Immune Cells Other Than Masmentioning
confidence: 81%